FAKTOR-FAKTOR YANG MEMPENGARUHI MARGIN PEMASARAN TERNAK SAPI POTONG DI KABUPATEN KUPANG - Ferdinan Suharjono Suek; Melkianus Dedimus Same Randu (Politeknik Pertanian Negeri Kupang, 2018)
The research aim’s to find the factors which influence the marketing margins of beef cattle in Kupang Regency. The research was conducted using a survey method. The research involved 94 respondentsas samples, consisted of 76 breeders, 12 intermediary traders, and 6 inter-island traders. Respondents of breeders were determined by simple random sampling, while intermediatery traders and inter-island traders were determined by snowballs sampling. The research data were collectedthrough direct observation and interview that use questionnaires. The results showed that the equation model Y = - 27,804 + 3,10X1 + 0,158X2. The coefficient of determination (R2) of 0.909 given overview of marketing margins which could be explained together on 90.9% by marketing costs and sales volume. The results of marketing testing cost and partial sales volume or as a whole showed a very significant effect (P <0.01) on marketing margins. In conclusion, the increase of marketing costand sales volume had contribution toward the marketing margin of beef cattle in Kupang Regency.